Developing business buccaneers: employer expectations of emergent leaders. Issue 5 (19th October 2016) - Tymon, Alex; Mackay, Margaret
Abstract : This study investigates employer expectations of graduates to inform pedagogical practice within a context of industry–university collaboration. Employers' views of graduates as future leaders are explored through interviews, focus groups and a survey, with a regional sample of 146 managers. Findings show employers have different understandings and diverse expectations of leadership traits and generic competencies. Employers anticipate future graduates will need greater adaptability and flexibility for volatile business contexts; with some highlighting rule breaking that implies a buccaneer approach rather than responsible leadership. The dissonance between an academic aim to educate socially responsible, global citizens and industry demands potentially undermines the coherence of partnership. Consequently, this study casts doubt on implicit assumptions that practice-informed, industry–university, collaboration will deliver better leaders. The main implications are that educators need to clearly communicate to employers how university learning transfers into actual work practice, and for graduates to better articulate their broad capabilities. The research offers fresh insight into on educators' responsibility to nurture critical thinking in graduates with the learning agility to question and responsibly navigate organisational rules. The study also contributes to the industry–university partnership debate by revealing the academic complexity of developing future leaders given the multiple lenses of practice-informed views.